Transport and Energy Research : a Behavioral Perspective - Zhang, Junyi (Elsevier, 2020)
Transport and Energy Research: A Behavioral Perspective deals with the transport issues associated with energy from a behavioral perspective in an interdisciplinary and systematic way. Existing transport and energy research has focused on technologies and energy efficiency; however, more efficient technologies do not necessarily lead to energy reduction. Unfortunately, very limited behavioral research can be found in the literature. This book covers major transport modes in major countries. It emphasizes the importance of researching the behaviors of not only transport and energy service users, but also transport and energy service providers, policy makers, organizations, company managers, and other stakeholders who are involved in and/or affected by transport and energy policies. It not only overviews the history of relevant research and presents new developments but also extensively discusses the future research issues. Various findings are summarized for reducing energy consumption from a behavioral perspective. This book provides readers with behavioral insights into more effective policymaking. Behavioral interventions are recommended as a key policy instrument for reducing energy consumption in a sustainable way. It provides policy makers with comprehensive insights into making more effective policies over the whole process of policymaking. The book can serve as a handbook for researchers and a textbook for graduate students in the fields of transport, energy, environment, planning, public policy, behavioral studies, and so on. --